Intermittent Parathyroid Hormone Accelerates Stress Fracture Healing More Effectively Following Cessation of Bisphosphonate Treatment - Mahmoud M Bakr; Wendy L Kelly; Athena R Brunt; Bradley C Paterson; Helen M Massa; Nigel A Morrison; Mark R Forwood (JBMR Plus, 2020)
ABSTRACT Parathyroid hormone (PTH) and bisphosphonates (BPs), including alendronate (ALN), have opposing effects on bone dynamics. The extent to which PTH remains effective in the treatment of stress fracture (SFx) in the presence of an ongoing BP treatment has not been tested. SFx was induced in 150 female Wistar rats, divided into five equal groups (n = 30). All rats were pretreated with ALN (1 μg/kg−1/day−1) for 14 days prior to SFx induction, followed by ALN cessation or continuation for the duration of the experiment; this was combined with daily PTH (8 μg/100 g−1/day−1) on SFx induction for 14 days, followed by cessation or continuation of ALN after SFx induction or an equivalent vehicle as a control. Ulnas were examined 2 weeks or 6 weeks following SFx. Two toluidine blue‐ and two tartrate‐resistant acid phosphatase‐stained sections were examined for histomorphometric analysis using Osteomeasure software. There was a significant interaction between the effects of time and treatment type on the woven bone width and apposition rate, as well as an improvement in the woven bone architecture. However, woven bone variables remained unaffected by the cessation or continuation of ALN. Cessation of ALN increased osteoclast number when compared with the ALN‐PTH continuation group (p = 0.006), and vehicle (p = 0.024) after 2 weeks. There was a significant interaction between the effects of time and treatment type on the number of osteoclasts per unit BMU area and length. The number of osteoclasts per unit BMU area and length was significantly greater in ALN cessation groups. It was concluded that intermittent short‐duration iPTH treatment effectively increased remodeling of SFx with a concurrent BP treatment, provided that BP was ceased at the time of SFx. Our results could help develop shorter iPTH treatment protocols for the clinical management of SFxs and guide clinical decision‐making to cease BP treatment in cases of SFx. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.